Case Shielding Efficiency, High Frequency Technology - Ruško, A.; Novikovs, V.; Balodis, G. (Elektronika ir Elektrotechnika, 2009)
We have presented the comparison of different electromagnetic (EM) shielding case vent shapes (different shape, but same surface) and estimate EM shielding efficiency for one mode E wave. EM shield is the integral part of the effective functioning devices. By changing type of the shape vent, it is possible to minimize EM impact. It is offered to value the shielding efficiency, by using scattering S matrix in analysis. Ill. 15, bibl. 8 (summaries in English, Russian and Lithuanian).